2011
DOI: 10.3109/02652048.2011.621554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PLGA hydrophilia on the drug release and the hypoglucemic activity of different insulin-loaded PLGA microspheres

Abstract: The effects of viscosity and hydrophilic characteristics of different PLGA polymers on the microencapsulation of insulin have been studied in vitro and in vivo after subcutaneous administration to hyperglycemic rats. Hydrophilic PLGA polymers produced a higher burst effect than the hydrophobic ones. Moreover, an incomplete insulin release was observed with the hydrophilic PLGA polymers in comparison with the hydrophobic ones. An explanation for that incomplete release can be the development of polymer-insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A small molecule added to a polymer matrix usually acts as a plasticizer that diminishes intermolecular interaction of the polymer and depresses Tg of the mixture from Tg of the pure polymer (Freed, 2011). Therefore, we considered that the DSC results in this study indicated an interaction between tacrolimus and PLGA (Achim et al, 2008;Presmanes et al, 2011;Sanchez et al, 1993). Based on the results for the entrapment efficiency and DSC, hydrophobic interaction and hydrogen bonding would be important for the entrapment of tacrolimus in microspheres.…”
Section: Characterization Of Tacrolimus-loaded Microspheresmentioning
confidence: 81%
“…A small molecule added to a polymer matrix usually acts as a plasticizer that diminishes intermolecular interaction of the polymer and depresses Tg of the mixture from Tg of the pure polymer (Freed, 2011). Therefore, we considered that the DSC results in this study indicated an interaction between tacrolimus and PLGA (Achim et al, 2008;Presmanes et al, 2011;Sanchez et al, 1993). Based on the results for the entrapment efficiency and DSC, hydrophobic interaction and hydrogen bonding would be important for the entrapment of tacrolimus in microspheres.…”
Section: Characterization Of Tacrolimus-loaded Microspheresmentioning
confidence: 81%
“…Given the significance and clinical development potential of aspirin, we combined it with TMZ to assay the treatment efficacy. PLGA was selected to prepare aspirin, TMZ, and aspirin-/TMZloaded microspheres as it was widely used as a carrier of microspheres to parcel drugs and to lengthen their sustained release time in the pharmaceutical industry [29][30][31]. In this study, we compared the antitumor effect of PLGA-aspirin, PLGA-TMZ, and PLGA -aspirin-TMZ microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Despite the slightly hydrophilic nature of the PLGA polymer used in this study due to its acid-terminated structure, its overall hydrophobic character allows it to function as a W/O emulsifier. [24] Moreover, it is important to note that viscosity plays a crucial role in emulsion stability. The decrease in interfacial tension facilitates the formation of smaller emulsions due to the reduced stress required for droplet breakup (Figure 2c).…”
Section: Stability Of Primary W/o Emulsion and Its Effect To Secondar...mentioning
confidence: 99%